The history of morris dancing, 1458-1750 - Forrest, John, 1951- (Studies in early English drama, 1999)
Careful, detailed, and encyclopedic, The History of Morris Dancing, 1458-1750 is an essential reference work for specialists in English drama and social historians of the period.